The Presence of Blastocystis in Tibetan Antelope (Pantholops hodgsonii) - Geng, Hong-Li; Sun, Yu-Zhe; Jiang, Jing; Sun, He-Ting; Li, Yuan-Guo; Qin, Si-Yuan; Wang, Zhen-Jun; Ma, Tao; Zhu, Jun-Hui; Xue, Nian-Yu; Ni, Hong-Bo (Frontiers in Cellular and Infection Microbiology, 2021)
Blastocystis is a protozoan that parasitizes the intestines. A number of hosts of Blastocystis have been found, including human and animals. However, there has been no research on the prevalence of Blastocystis in Tibetan Antelope. Here, a molecular test was performed using 627 Tibetan Antelope fecal samples collected on Tibet in China from 2019 to 2020. The result showed that 30 (4.8%) samples were Blastocystis positive. The highest prevalence of Blastocystis was in Shuanghu County (25/209, 12.0%), and followed by Shenza County (2/103, 1.9%), Nyima County (3/182, 1.6%), and Baigoin County (0/133, 0.0%). In addition, logistic regression analysis showed that the gender, sampling year, and area of Tibetan Antelope were risk factors for Blastocystis prevalence. Three subtypes (ST10, ST13, and ST14) of Blastocystis were found in Tibetan Antelope through a subtype sequence analysis, and ST13 was identified to be the dominant subtype. This is the first investigation for the infection of Blastocystis in Tibetan Antelope. Collectively, the data in this study have expanded the host range of Blastocystis, and provided basic information for the distribution of Blastocystis subtypes, which could support for the prevention of Blastocystis infection in wild animals.